2015
DOI: 10.1177/0963947015585228
|View full text |Cite
|
Sign up to set email alerts
|

Code-switching in Italo-Brazilian literature from Rio Grande do Sul and São Paulo: A sociolinguistic analysis of the forms and functions of literary code-switching

Abstract: Italo-Brazilian prose texts from São Paulo and Rio Grande do Sul, written from the 1920s until today, either in Brazilian Portuguese with Italian code-switches, or in the Venetian koiné spoken by the Italian immigrants in Rio Grande do Sul, sometimes switching to Portuguese, are an early, but so far largely neglected example of literary code-switching representing the multilingual immigrants’ communities. In a sociolinguistic analysis of these texts I will argue that the conversational functions of literary co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 15 publications
0
11
0
1
Order By: Relevance
“…Gardner-Chloros and Weston (2005) focused on the differences and similarities between the functions of codeswitching in spoken and written forms. Müller (2015) opined that though the stylistic function of code-switching played a major role in the literature on a micro-level, yet on the macro-level that kind of code-switching could be considered to be a response to bilingual identity. Many aspects of code-switching and code-mixing between Hindi and English have also been studied (Chetia, 2017;Sailaja, 2011).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Gardner-Chloros and Weston (2005) focused on the differences and similarities between the functions of codeswitching in spoken and written forms. Müller (2015) opined that though the stylistic function of code-switching played a major role in the literature on a micro-level, yet on the macro-level that kind of code-switching could be considered to be a response to bilingual identity. Many aspects of code-switching and code-mixing between Hindi and English have also been studied (Chetia, 2017;Sailaja, 2011).…”
Section: Review Of Literaturementioning
confidence: 99%
“…6 Por su reconocida capacidad para expresar significado social, discursivo y referencial (Heller, 1988, p. 2) el CdC es un recurso narrativo útil que da a la escritura lo que en inglés se denomina "local colour", creando simbólicamente "a sense of place" (Gardner-Chloros, 2010, p. 507). Muchos investigadores (Callahan, 2004;Montes-Alcalá, 2015;Müller, 2015;Sebba, 2000;Sebba et al, 2012, entre otros) han demostrado que los escritores lo usan como apoyo para resaltar la representación de los personajes (Jonsson, 2010(Jonsson, , p. 1309, como estrategia creativa para mostrar la identidad (Cortés-Conde y Boxer, 2002, p. 137), indicar una cultura compartida o bien para crearla (Heller, 1988, pp. 270-71).…”
Section: En Torno Al Cambio De Código Y El Uso De Hispanismosunclassified
“…They have also focused on the differences and similarities between the functions of codeswitching in spoken and written forms, and concluded that the functions are similar in both modalities and also extend to other semiotic systems like sign language and visual culture. Müller (2015) also discussed examples of literary code-switching in selected Italo-Brazilian texts to highlight the relationship between the forms and functions of literary multilingualism and their sociolinguistic implications and concluded that though the stylistic function of code-switching played a major role in literature than in other genres on a micro-level, yet on the macro-level that kind of code-switching could be considered to be a response to bilingual identity.…”
Section: Motivation For Studymentioning
confidence: 99%